Physical characterization of plastic and paper in the domestic solid waste district of La Molina , according to socioeconomic strata - Espinoza Farfán, Eduardo (2012)
Physical analysis of solid waste , particularly plastic and paper, from domestic urban waste are a concern because they are the most available and discarded , so abundant in the middle. The study helps determine the extent of this problem that , although the evolution of the industry , customs and technology , has meant that today there is a different quality of new products, especially from the packaging . The population was located in the district of La Molina , by socioeconomic strata , this study has provided accurate , that would generate improvement projects , commercial development and urban development in the search for a better quality of life information. The technical arguments and information to visualize the problem and propose solutions for urban and healthy development of the town , serving as impact to the great city of Lima and the like surrounding .